Gobierno corporativo, profesionalización y plan de sucesión para la Empresa ATAI de Tibás Ltda. - Jiménez-Sánchez, Juan Carlos; Piedra-Abarca, Hernán José; Zamora-Salazar, Diego (Instituto Tecnológico de Costa Rica, 2017)
The following project is developed in ATAI of Tibás Ltda. Family business, which is dedicated to sale technical articles for the areas of art, surveying, architecture and engineering (hence its name). Main purpose of paper is to propose governing structures, succession and retirement plans, using best practices for family businesses, to improve management efficiency and guarantee business continuity. Document is divide in five main chapters structured as follows: First chapter entitled Generalities covers company background, approach, research problem, justification, objectives, closing with scope and limitations. Second chapter is the Theoretical Framework which focus on explaining relevant theoretical elements in topics of: family business, roles, decision making, conflict management, perspectives, governance bodies, governance structures, leadership, succession, professionalization and research methodology. Chapter three is Methodological Framework which explains procedures and instruments used during development of the project. It details information gathering tools used internally within the company and how results were used to approach the proposals. Chapter four called Diagnosis focus on aspects within the company and family, specifically on aspects relevant to governance structures, retirement plans and succession, concluding with presentation of strengths, weaknesses, opportunities and Threats (SWOT). Once diagnosis is made, Proposals are elaborated in chapter five, which outlines practices, governing bodies, succession, retirement plans and roles for the business family. Finally, document closes with conclusions and recommendations derived from diagnosis and proposals made respectively.
Proyecto de Graduación (Maestría en Dirección de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2017.
Keywords: Sector comercial; Gestión de negocios; Toma de decisiones; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies